2021
DOI: 10.1186/s40360-021-00517-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the toxic threshold of 3-hydroxybutyrate-sodium supplementation in septic mice

Abstract: Background In septic mice, supplementing parenteral nutrition with 150 mg/day 3-hydroxybutyrate-sodium-salt (3HB-Na) has previously shown to prevent muscle weakness without obvious toxicity. The main objective of this study was to identify the toxic threshold of 3HB-Na supplementation in septic mice, prior to translation of this promising intervention to human use. Methods In a centrally-catheterized, antibiotic-treated, fluid-resuscitated, parente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The racemic mixture of 3HHB reached a maximal effect on muscle force at 40 mmol/kg/day, the same dose at which 3HB-Na reached its maximal effect 10 . However, as one molecule of 3HHB can be metabolized to two molecules of 3HB, this difference in efficacy might point to an incomplete metabolism of 3HHB.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The racemic mixture of 3HHB reached a maximal effect on muscle force at 40 mmol/kg/day, the same dose at which 3HB-Na reached its maximal effect 10 . However, as one molecule of 3HHB can be metabolized to two molecules of 3HB, this difference in efficacy might point to an incomplete metabolism of 3HHB.…”
Section: Discussionmentioning
confidence: 80%
“…In these previous studies, the ketone body was administered as daily subcutaneous bolus injections of a racemic mixture of d , l -3-hydroxybutyrate sodium salt (3HB-Na). However, an escalating dose-finding study revealed that the effective dose of 40 mmol/kg/day of 3HB-Na was close to the toxic threshold 10 . Indeed, augmenting the daily dose with 20% or more increased severity of illness, markers of vital organ damage and mortality, in part explained by excessive Na + intake.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…KEs induced mild acidosis shortly after administration and did not significantly affect blood pH in the long term 23,26 . Attributing the alkalizing effect of KSs to its cation load is further substantiated by KS toxicology studies in mice, which found a quick intracellular uptake of βHB from the circulation, whereas the accompanying Na + remained 27 . This cation load may limit the tolerability of KSs, since dosages needed to treat adults with FAODs are relatively high.…”
Section: Discussionmentioning
confidence: 98%
“… 23 , 26 Attributing the alkalizing effect of KSs to its cation load is further substantiated by KS toxicology studies in mice, which found a quick intracellular uptake of βHB from the circulation, whereas the accompanying Na + remained. 27 This cation load may limit the tolerability of KSs, since dosages needed to treat adults with FAODs are relatively high. Although previous studies have shown therapeutic benefits of KS supplementation in pediatric patients, alternative forms of βHB without a salt load (e.g., KEs) might be more suitable to adults.…”
Section: Discussionmentioning
confidence: 99%